Partial Purification and Characterization of Xylanase from Bacillus weihenstephanensis Strain ANR1 using Watermelon Rind - Annie Deborah Harris, S (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of this study is to partially purify and characterize xylanase from Bacillus weihenstephanensis strain ANR1 using watermelon rind as a substrate. Materials and Methods: The soil bacterium, B.weihenstephanensis strain ANR1 was grown at 37Â°C for 72 h on rotary incubator shaker at 150 rpm in a flask containing 250 ml of medium. The xylanase enzyme was partially purified using ammonium sulfate precipitation and dialysis. It was further purified using DEAE-sepharose chromatography. Molecular weight of the xylanase enzyme was determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Results and Discussion: The xylanase enzyme was partially purified to a fold of 8.15 and a yield of 83.56%. Molecular weight of the protein was found to be 45 kDa. The purified enzyme was found to be optimally active at pH of 7.0 and at a temperature of 37Â°C. Conclusion: Based on the results obtained, the purified xylanase enzyme from B. weihenstephanensis strain ANR1 using watermelon rind as a substrate can be effectively used in various food industrial applications